MENINGKATKAN MOTIVASI BELAJAR DARING MELALUI LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK NUMBERED HEADS TOGETHER PADA SISWA KELAS VIII H SMP NEGERI 1 JATI KUDUS - Apriliani, Nike Arditha; Zamroni, Edris; Santoso, Santoso (Jurnal Muria Research Guidance and Counseling (MRGC), 2023)
The research objectives were to describe and to learing impact and implementation of group guidance services to increase online learning motivation in class VIII H students at SMP Negeri 1 Jati Kudus in the 2022/2023 academic year. The research used was Guidance and Counseling Action Research (PTBK) with 8 students as research subjects. The results of the research on pre-cycle online learning motivation get an average score of 10 with a percentage of 30%. Whereas in cycle I got an average score of 18 percentages 54%. Whereas in cycle II, an average score of 30 percentages is 90%. In the implementation of group guidance services with Numbered Heads Together, the results of observations of researchers were carried out during group guidance which obtained results in the first cycle of researchers getting a score of 20 percentages, 60%. Meanwhile, in cycle II, a score of 29 percentages 87%. In conclusion, the results of the study showed an increase in online learning motivation after being given group guidance services with Numbered Heads Together to class VIII H students of SMP N 1 Jati Kudus, which was acceptable, this was proven after the implementation of group guidance services with Numbered Heads Together there was an increase of 87% from cycle I to cycle II while in online learning motivation there was an increase of 90% from pre-cycle to cycle II.